A clinical study of corneal complications of cataract surgery - ., Anjana; Padmaja, N. L.; Sundararajan, D.; Bhuvaneshwari, K. Namitha; ., Manjunathan (International Journal of Advances in Medicine, 2020)
Background: In this study we investigate the incidence of corneal complications of extra capsular cataract extraction (ECCE) and manual small incision cataract surgery (SICS). We study the various etiological factors leading to these complications and also to highlight various prophylactic intra and post-operative measures to reduce these complications. Methods: Cataract surgery was conducted on 100 patients at Meenakshi Medical College Hospital and Research Institute. Patients were randomly divided into two groups. Group A of 50 patients were subjected to ECCE with posterior chamber intraocular lenses (PCIOL) and group B of 50 patients to small incision cataract surgery with PCIOL. Results: On the first post-operative day, 5 post-operative cases developed corneal edema (10%) in ECCE and 4 cases (8%) in SICS. Striate keratitis developed in 4 cases of ECCE (8%) and 3 SICS (6%). Nearly 62% patients who underwent ECCE accepted cylinder between 0.25-0.75 D while there were 52% cases in SICS. Conclusions: In this study we conclude that with various advances in cataract surgery the incidence of corneal complication have reduced and have helped in early visual rehabilitation and minimization of post-operative astigmatism by careful selection of incision type and location for MSICS.